The effect of inoculation with Lactobacillus spp. on the production of 1,2-propanediol and 1-propanol, hygienic quality and aerobic stability of maize silage - Selwet, Marek (Polish Journal of Agronomy, 2021)
The aim of the study was to determine the influence of a commercial bacterial inoculant PK (Lactobacillus plantarumK KKP/593/p, L. plantarum C KKP/788/p, L. brevis KKP 839, L. buchneri KKP 907) and a ML preparation (L. buchneri ATCC 4005, L. diolivorans LGM 19667, L. reuteri ATCC 23272) on the concentration of 1,2-propanediol and short-chain fatty acids (acetic acid, propionic acid ) on maize silage aerobic stability pro-longation. The silage was prepared in laboratory microsilos with a capacity of 10 dm3. The basic composition of the feed was de-termined according to the AOAC. The measure of oxygen stabi-lity was the time needed to raise the silage temperature by ≥2 ̊C about the ambient temperature.The research showed that during 120-day ensilage, the ap-plied preparations significantly (p<0.05) reduced the content of dry matter, water-soluble sugars and pH. The concentration of lactic acid, acetic acid and propionic acid in the inoculated sam-ples increased significantly. 1,2-propanediol and 1-propanol were not found in control silages. The addition of PK and ML signifi-cantly increased the concentration of these substances. The num-ber of lactic acid bacteria in silage with biological additives was significantly higher, and the number of yeasts and mould fungi was lower compared to the control. The applied mixtures of PK and ML significantly extended the time of aerobic stability of si-lages.